Negara dan Ilegalitas: Studi Kasus Perdagangan Burung di Wilayah Jakarta - Indraini Hapsari; Semiarto Aji Purwanto (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2020)
This article aims to analyze the relationship between state and illegality which taking place at the center, namely in Jakarta. The study becomes significant for examining how mechanisms and relations of non-state and state actors occur. Many ethnographic studies of illegal activities, such as gold mining, logging, and fishing show that such businesses take place on the periphery or border where the state has weak control over such places. Data is conducted by literature study and short field observations.Our case studies of illegal trade in the bird market in Jakarta will question the Weberian perspective which defines the state as a legal and rational institution that will always enforce control in its territory. In this article, we consider the state as a relational arena where it is possible for various actors, both non-state and state actors, to participate in illegal activities through contestations or collaboration to achieve their respective interests or goals.